A Case Series Describing The Cytomorphology And Clinical Features Of Follicular Dendritic Cell Sarcoma. (28th October 2020) - Bailey, C A; Weimholt, R C
Abstract: Introduction/Objective: Follicular dendritic cell sarcoma (FDCS) is the malignant counterpart of the germinal center follicular dendritic cell. Cytomorphological descriptions are few, with only 24 prior cytology reports from 22 publications. We present 4 cases with the aim of adding to this small body of literature. Methods: Our database was searched for "dendritic cell." Patients diagnosed with FDCS that had a cytology specimen were included. Clinical and cytologic features were tabulated. Results: Case 1 was an 87-year-old man with a retroperitoneal mass. Aspiration rendered a new diagnosis of FDCS, supported cell block immunohistochemistry. Case 2 was an aspiration of metastatic FDCS to the lung in a 40 year-old- man with a known neck primary. Case 3 was a 46-year-old-man with a left neck mass. Aspiration rendered a misdiagnosis of "atypical epithelioid cells in a background of granulomatous inflammation". Subsequent needle biopsy confirmed FDCS. Case 4 was an aspiration of metastatic FDCS to the liver in a 66 year-old-woman with a known splenic primary. Comparison of cytomorphology show identical features in all cases. Smears were hypercellular and composed of variably sized syncytial aggregates as well as individually dispersed cells. Tumor cells were variably epithelioid to spindled, had fine chromatin and small nucleoli, displayed frequent bi- and multinucleated forms, and had abundant pale cytoplasm with long, slender fibrillar processes. All cases demonstrated many small lymphocytes intermixed both within the syncytial aggregates and dispersed in the background. Conclusion: Cytomorphological features of FDCS appear conserved from case to case. Knowledge of these features may aid in its recognition in aspiration material.